"What Should Sex Look Like?" Students' Desires for Expanding University Sexual Assault Prevention Programs to Include Comprehensive Sex Education. (November 2019) - Hubach, Randolph D.; Story, Chandra R.; Currin, Joseph M.; Woods, Audrey; Jayne, Ashlee; Jayne, Christopher
Rates of sexual assault and sexual violence among college-aged adults are much higher than the national rates of sexual assault and sexual violence. Therefore, reduction and prevention of sexual violence among university students is critical and is consistent with national public health priorities. Often times, messages to students focus only on sexual assault and omit larger notions of sexual health. Four focus groups with a total of 24 participants (nine men, 15 women) highlighted three main perceptions about the sexual assault programming offered at this large university: themes of resistance to traditional programming, a need for holistic sexual health programming, and a desire to have an environment, which normalizes conversations surrounding sex, sexuality, and sexual health.